Antitumoural immunity by virus-mediated immunogenic apoptosis inhibits metastatic growth of hepatocellular carcinoma. Issue 10 (30th July 2010) - Boozari, Bita; Mundt, Bettina; Woller, Norman; Strüver, Nina; Gürlevik, Engin; Schache, Peter; Kloos, Arnold; Knocke, Sarah; Manns, Michael P; Wirth, Thomas C; Kubicka, Stefan; Kühnel, Florian
Abstract : Background and aims: Viral infection of a dying cell dictates the immune response against intracellular antigens, suggesting that virotherapy may be an effective tool to induce immunogenic cell death during systemic cancer treatment. Since viruses and proteasome inhibitors both induce accumulation of misfolded proteins, endoplasmic reticulum (ER) stress and immune responses during treatment of hepatocellular carcinoma (HCC) with bortezomib and the tumour-specifically replicating virus hTert-Ad (human telomerase reverse transcriptase promoter-regulated adenovirus) were investigated. Methods: Unfolded protein response (UPR) pathways and ER stress-mediated apoptosis were investigated by western blots, caspase-3 assays, 4', 6-diamidino-2-phenylindole (DAPI) and Annexin V staining in HCC cells following hTert-Ad/bortezomib treatment. Oncolysis was assessed in subcutaneous HCC mouse models. Antiviral/antitumoural immune responses were characterised in immunocompetent HCC mouse models by ELISA, ELISpot assays and pentamer staining. Systemic efficacy of antitumoural immunity was investigated by determination of lung metastases burden. Results: Bortezomib and hTert-Ad trigger complementary UPR pathways but negatively interfere with important recovery checkpoints, resulting in enhanced apoptosis of HCC cells in vitro and improved oncolysis in vivo. In immunocompetent mice, bortezomib inhibited antiviral immune responses, whereas ER stress-induced apoptosis of infected HCC resulted in caspase-dependent triggering of antitumoural immunity. In therapeutic settings in immunocompetent, but not in immunodeficient or CD8-depleted mice, virotherapy-induced antitumoural immunity efficiently inhibited outgrowth of non-infected lung metastases. Immunotherapeutic efficacy could be significantly improved by bortezomib in experiments with low viral doses. Conclusion: Proteasome inhibition during virotherapy disrupts the UPR, leading to enhanced ER stress-induced apoptosis, improved local oncolysis and antitumoural immunity. The results suggest that combining intratumoural virotherapy with adjuvant systemic therapies, which specifically support the function of the virotherapy as an antitumoural vaccine, is a promising immunotherapeutic strategy against HCC.